Acquisition of Slovene as a Second or Foreign Language in an Intercultural Context on the Example of Selected Originally Slovene Works of Fiction - Pulko, Simona; Zemljak Jontes, Melita (Slavia Centralis, 2023)
As a constantly developing ability of an individual, reading literacy is key to the understanding, critical evaluation and use of written information, and is the basis for all other types of literacy when acquiring a native or non-native (second or foreign) language. While all the components of reading literacy are important, this paper emphasizes the 4th, 5th, 8th and 9th components. Selected originally Slovene works of fiction (Moj prijatelj je drugačen; Ali te lahko objamem močno?) are analyzed from a cross-cultural and linguistic points of view, taking into consideration basic information about the works themselves through the prism of didactic orientations, and with a critical view of the didactic instruments prepared by the authors themselves